Conditioning program prescribed from the external training load corresponding to the lactate threshold improved cardiac function in healthy dogs - Restan, Alejandro Zamora [UNESP] (2022)
This research focuses on the adjustments in systolic and diastolic functions that are not fully understood in dogs submitted to athletic training. Beagle dogs carried out an endurance training program (ETP) prescribed from the external training load, corresponding to 70–80% of the lactate threshold (VLT) velocity. Eighteen dogs were randomly assigned to two groups: control (C, n = 8), active dogs that did not perform any forced exercise, and trained (T, n = 10), submitted to the ETP during eight weeks. All dogs were evaluated before and after the ETP period using two-dimensional echocardiography, M-mode, Doppler, and two-dimensional speckle tracking. A principal component analysis (PCA) of the echocardiographic variables was performed. The ETP improved the left ventricular internal dimension at the end of diastole (LVDd), the left ventricular internal dimension at the end of diastole to aorta ratio (LVDd: Ao), and the strain rate indices. PCA was able to capture the dimensionality and qualitative echocardiography changes produced by the ETP. These findings indicated that the training prescribed based on the lactate threshold improved the diastolic and systolic functions. This response may be applied to improve myocardial function, promote health, and mitigate any injuries produced during heart failure.